2019
DOI: 10.9734/ajrcs/2019/v4i230071
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Response of Bush Bean (Phaseolus vulgaris L.) as Influenced by Different Levels of Nitrogen and Phosphorus Application

Abstract: The experiment was conducted at Horticulture Farm at Sher-e-Bangla Agricultural University, Bangladesh during the period December, 2014 to March 2015 to evaluate the effect of different levels of nitrogen and phosphorous on the growth and yield of bush bean. The two factor experiment was laid out in Randomized Complete Block Design with three replications. The treatment was comprised of two factors-Factor A: levels of nitrogen i) 0 kg/ha, ii) 20 kg/ha, iii) 40 kg/ha and Factor B: levels of phosphorous (P 2 O 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
2
7
0
Order By: Relevance
“…The highest length of the green pod was found (11.15 cm) in treatment N 80 which is statistically identical with N 40 , N 120 treatments and the lowest (10.30 cm) was found in the plot treated with N 0 treatment ( Table 1). This result is in full agreement with several authors [22,23]. They reported that pod length was significantly influenced by optimum dose of N. Nitrogen is a part of the chlorophyll molecule which activates the normal metabolic process of leaves.…”
Section: Pod Lengthsupporting
confidence: 93%
See 2 more Smart Citations
“…The highest length of the green pod was found (11.15 cm) in treatment N 80 which is statistically identical with N 40 , N 120 treatments and the lowest (10.30 cm) was found in the plot treated with N 0 treatment ( Table 1). This result is in full agreement with several authors [22,23]. They reported that pod length was significantly influenced by optimum dose of N. Nitrogen is a part of the chlorophyll molecule which activates the normal metabolic process of leaves.…”
Section: Pod Lengthsupporting
confidence: 93%
“…The lowest on pod yield plot -1 (1454.17 g) was found in control treatment (Table 1). Similar result was found by several authors [22,27]. On the other hand Gomez and Gomez [21] found significantly influenced by optimum dose of nitrogen on green…”
Section: Pod Yield Plot -1supporting
confidence: 91%
See 1 more Smart Citation
“…The center of origin of this crop is South America but consumed in all parts of the globe for its edible seeds and pods [2]. Being a major grain legume crop of the world it is a resourceful short-duration legume crop with high grain yielding potential and diversified use [3]. It can be used both as pulses and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known as the french bean, kidney bean, common bean, basic bean, snap bean, raj bean, navy bean, haricot bean, string bean, pole bean, wax bean and bonchi [5]. The marketable parts of this fruit are immature green pods and marketed either in fresh or in frozen or canned condition [3]. The dry seeds also may be used as pulses for human consumption or animal feed.…”
Section: Introductionmentioning
confidence: 99%